A Study of Financial Services Marketing: Exploring the Evolution of Customer Relationship in Retail Banking (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thetraditional notion of the retail bank clerk who is intimately   knowledgeable   about  a   customer’s   banking  needs   and   who personally knows the customer may nolonger be a typical part of the banking experience.   In such an environment, it is imperativethat financial services marketers find innovative ways to create loyalty andtrust among their customer base and provide the personal touch that may beneeded to retain customers.